Didactic Analysis of School Volleyball Teaching in Tunisia Case Study of two Specialist and Non-Specialist Teachers (London Journal of Research In Humanities and Social Sciences, 2024)
The article attempts to identify the effect of the teachers’ speciality on their didactic activity in relation to the knowledge taught and to describe and analyse the verbal interventions of physical education and sports teachers (volleyball specialist/non-specialist) during the teaching-learning session. After specifying our theoretical framework, which is partly based on the semiotic approach, we specify our data collection methodologies (observation grid, video recordings, interviews), focusing particularly on the teachers’ intervention practices. Among the results obtained, we show how his verbal activity is coherent with his professional representations while also resulting from a major importance of the PE teacher’s specialty that he is led to perfect his professional practices.
Keywords: teaching practices; school volleyball; verbal intervention; didactic regulation